WELL-BEING IN LATE STAGE DEMENTIA: HOW WILL WE KNOW IT WHEN WE SEE IT?. (11th November 2018) - Kolanowski, A M
Abstract: Longer lives often involve complex care issues to maintain the health of older adults. Dementia poses some of the more difficult complex care issues, including strategies to address psychiatric behaviors and drug burden, both in community and nursing home residents. At the same time, gerontologic interventions offer great promise for addressing these challenges, including non-pharmacological interventions for the behavioral symptoms of dementia and delirium.